A política externa de Shinzō Abe (2012-2019) e o novo caminho japonês - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The present research has as it´s main objective to investigate Shinzō Abe's foreign policy (2012-2019) and its geopolitical consequences, taking into account remilitarization and economic reforms, as well as the different Japanese international relations with its geographical environment, during the period of 2012 to 2019. In order to be able to understand the current Japanese state, a historical approach will be used, going through the formation and the end of the imperialist state, as well as the construction and modifications of the pacifist state since its creation in 1947. Throughout the Japanese imperial period, it was possible to see important factors such as nationalism, the instrumentalization of the Shinto religion and Japanese militarization. By contrast, in the Pacifist State during the Cold War it was seen a greater focus on economic growth, causing in the 1990s the deterioration of Japanese foreign policy and the strengthening of the Japanese polarization between those favoring remilitarization and the opposite. Shinzō Abe's Japan, from 2012 to 2019, has presented itself as a state that tries to stabilize economically, remilitarize itself in the face of changes in the Asia-Pacific region and blending past issues into the present, building a new Japanese path. During this work, concepts inherent to Japan are used for a better examination of the object of study. Through a methodology based on the qualitative approach, the hypothetical-deductive analysis, the historical-descriptive procedure and a broad bibliographic framework, using newspapers, books, articles and official documents, it was intended to achieve the objectives proposed by this research.
Shinzō Abe's foreign policy (2012-2019) and the new Japanese way
Keywords: Japão; Shinzō Abe; Remilitarização; Constituição de 1947; Império Japonês; Japan; Remilitarization; Constitution of 1947; Japanese empire; CNPQ::CIENCIAS SOCIAIS APLICADAS